'THE PAST NO LONGER CASTS LIGHT UPON THE FUTURE; OUR MINDS ADVANCE IN DARKNESS'1: THE IMPACT AND LEGACY OF SIR ALEC CLEGG'S EDUCATIONAL IDEAS AND PRACTICES IN THE WEST RIDING OF YORKSHIRE (1945-1974). Issue 3 (4th May 2021) - Wood, Margaret; Pennington, Andrew; Su, Feng
ABSTRACT: This paper examines and evaluates some aspects of the legacy of the West Riding of Yorkshire County Council and its long serving Chief Education Officer, Sir Alec Clegg, who held the post between 1945 and 1974. Against a subsequent political discourse of markets, choice and autonomy which portrays local authorities as the cause of poor educational outcomes and school failure, political developments have led to a diminution of the role of local authorities, destruction of local democratic accountability and greater centralisation of power and control of education. Drawing on interviews and email correspondence with former pupils, teachers, officers and others of the West Riding, its successor authorities and beyond, we explore the context, tensions, successes and lasting impact of Clegg's ideas and practice, particularly in relation to support for community development and the arts and creativity. The paper also looks at Clegg's influence and legacy with regard to selection for secondary education and the role of middle schools, the development of primary education and the impact on successor authorities to the West Riding and beyond.